Pembangunan Kelembagaan Pinjaman Dana Bergulir Hutan Rakyat - Bramasto Nugroho (Jurnal Manajemen Hutan Tropika, 2010)
Community forest (hutan rakyat, HR) in Java and Madura Island has been rapidly increasing. During 2003–2010 period, the average increment of HR was 200,000 ha year-1. Due to that, Ministry of Forestry wants to expand the financing services not only to community forest plantation through revolving fund scheme called as PDB-HTR (outside Java), but also to the development of community forest through a revolving fund scheme called as PDB-HR (in Java). Expansion of this service is basically an institutional development effort means improvement of the rules of the game (i.e. credit scheme) and player of the game (organizations). Analysis on this paper is directed to provide input for the institutional development for PDB-HR by the use of 5 approaches to institutional development, and institutional analysis and development framework (IAD). The results showed that there was a need to improve PDB-HTR scheme, including the basis of loan calculation, credit rationing, the target group, the credit ceiling, and the payment system. Based on institutional perspective, some principles that should be followed to support the poor to access the credit were simplicity, accessibility, conformity, feasibility, sustainability, transparancy, supervisory, assisting and facilitating, and learning.